Diplomas, Photos, andTchotchkesas Symbolic Self-Representations: Understanding Employees' Individual Use of Symbols - Byron, Kris; Laurence, Gregory A. (Academy of Management Journal, 2015)
Most employees personalize their workspaces with photos, memorabilia, and other items—even in the face of constraints such as rules prohibiting personalization. This prevalent use of objects likely reveals much about intrapersonal and interpersonal processes at work. By analyzing employee interviews and workspace inventories and observations, we discover that the objects with which employees personalize their workspaces (and even the absence of such objects) symbolize who they are and who they want to be. Through their symbolic representations of self, they find common ground (often through shared nonwork experiences), establish a common understanding of employees' work roles, and share personalistic information about the self—all of which contribute to relationship development among employees and their coworkers, customers, and clients. With symbolic representations of self that offer an optimal amount of stimulation, they focus their attention on their goals and values and establish a desired boundary or integration between work and nonwork—both of which contribute to employees' self-regulation. Our findings support the importance of examining micro-level processes related to the physical work environment, as we find that employees shape their work environment in ways that affect both their relationships at work and their self-regulatory functions.